Analysis and Design of Monolithic System Architecture Migration to Microservices at PT. MALINDO Conceptual Approach - Ego Oktafanda; Nofri Wandi Al-Hafiz; Abdul Latif; Firman Santosa (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
This study analyzes the transition from a monolithic architecture to a microservices architecture within a corporate environment, specifically at PT.MALINDO. While the monolithic architecture was once effective, it now presents several challenges, including maintenance complexity, limited scalability, and frequent occurrences of deadlocks. The analysis highlights the growing need for a more adaptive and flexible system to respond to dynamic business requirements. In this context, a microservices architecture is proposed as a solution to overcome the limitations of the monolithic approach. Microservices break down applications into small, independent services, enabling easier and more efficient development, deployment, and maintenance. By using components such as an API Gateway and message brokers like Apache Kafka, inter-service communications can be managed more effectively, ensuring improved system performance and resilience. The findings indicate that transitioning to a microservices architecture can significantly enhance the system's performance, flexibility, and scalability. The resulting hypothesis suggests that adopting microservices will offer long-term benefits for PT.MALINDO, particularly in addressing system complexity and improving responsiveness to evolving business needs. Recommendations include implementation strategies and change management practices necessary to ensure a smooth and low-risk transit